2000
DOI: 10.1159/000028959
|View full text |Cite
|
Sign up to set email alerts
|

MR Venography in Children with Complex Craniosynostosis

Abstract: Purpose: Chronic venous hypertension due to jugular foramen stenosis has been proposed as an etiology for the hydrocephalus and tonsillar herniation seen in some patients with complex craniosynostosis. We report the use of MR venography (MRV) to evaluate venous outflow obstruction in this clinical setting. Materials and Methods: We studied 17 patients, (ages 4 months to 34 years; mean 7.3 years) with complex craniosynostosis; 8 patients with Crouzon’s syndrome, 2 with Apert’s, 1 with Pfeiffer’s and 6 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 12 publications
0
46
0
Order By: Relevance
“…Showing the prevalence of posterior condylar fossae and posterior condylar foramina according the left and right sides. Rollins et al (2000) reported that the condylar foramen was found in 60% of the specimens studied. They were more frequently found on the right side than on the left side and Muthukumar et al report the condylar foramen was found in 60% of the specimens studied.…”
Section: Discussionmentioning
confidence: 94%
“…Showing the prevalence of posterior condylar fossae and posterior condylar foramina according the left and right sides. Rollins et al (2000) reported that the condylar foramen was found in 60% of the specimens studied. They were more frequently found on the right side than on the left side and Muthukumar et al report the condylar foramen was found in 60% of the specimens studied.…”
Section: Discussionmentioning
confidence: 94%
“…4,9,10,43 Children with craniofacial disorders as well as hydrocephalus are more likely to have a CM than children with a craniofacial disorder in the absence of hydrocephalus. 4,9,34 Hydrocephalus has also been reported to develop after repair of craniosynostosis, with subsequent development of tonsillar herniation. 9,43 In our own series, 4 of the 5 patients with de novo CM on serial imaging developed hydrocephalus after craniosynostosis repair and were treated with VP shunt placement prior to the CM diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Hydrocephalus, venous hypertension, and associated congenital brain anomalies have also been proposed as possibly important factors leading to CM development in these patients. 5,34,39,40 The optimal management of CM in the setting of craniosynostosis is not well established. Some surgeons advocate simultaneous surgical correction of craniosynostosis and CM, and others suggest that CM should only be treated if it is symptomatic or associated with a syrinx.…”
mentioning
confidence: 99%
“…2,3,11 These fusions result in diminished cranial volumes, with small posterior fossae predisposing this population to cerebellar tonsillar herniation and its potential consequences. 12,13,17,18 These findings distinguish these patients from those in the general population with Chiari malformation Type I.…”
Section: ©Aans 2013mentioning
confidence: 72%